Plant Glycobiology - a sweet world of lectins, glycoproteins, glycolipids and glycans - Nausicaa Lannoo (Frontiers Research Topics, 2014)
Plants synthesize a wide variety of unique glycan structures which play essential roles during the life cycle of the plant. Being omnipresent throughout the plant kingdom, ranging from simple green algae to modern flowering plants, glycans contribute to many diverse processes. Glycans can function as structural components in the plant cell wall, assist in the folding of nascent proteins, act as signaling molecules in plant defense responses or (ER) stress pathways, or serve within the energy metabolism of a plant. In most cases, glycans are attached to other macromolecules to form so-called glycoconjugates (e.g. glycoproteins, proteoglycans and glycolipids), but they can also be present as free entities residing in the plant cell. Next to the broad, complex set of glycans, plants also evolved an elaborate collection of lectins or proteins with a lectin-like domain, which can recognize and bind to endogenous (plants-own) or exogenous (foreign) glycans. Though still poorly understood in plants, the dynamic interactions between lectins and carbohydrate structures are suggested to be involved in gene transcription, protein folding, protein transport, cell adhesion, signaling as well as defense responses. As such, a complex and largely undetermined glycan-interactome is established inside plant cells, between cells and their surrounding matrix, inside the extracellular matrix, and even between organisms. Studying the biological roles of plant glycans will enable to better understand plant development and physiology in order to fully exploit plants for food, feed and production of pharmaceutical proteins. In this Research Topic, we want to provide a platform for articles describing the latest research, perspectives and methodologies related to the fascinating world of plant glycobiology, with a focus on following subjects: 1. Identification and characterization of plant glycans, their biosynthetic and degradation enzymes 2. Characterization of plant lectins and glycoproteins 3. Plant glycans in the plant's energy metabolism 4. Role of plant glycans in plant defense signaling 5. Use of plant lectins in pest control 6. Plant lectins as new tools in human medicine 7. Glyco-engineering in plants